Language Mapping Using Stereo Electroencephalography: A Review and Expert Opinion - Aron, Olivier; Jonas, Jacques; Colnat-Coulbois, Sophie; Maillard, Louis (Frontiers in Human Neuroscience, 2021)
Stereo-electroencephalography (sEEG) is a method that uses stereotactically implanted depth electrodes for extra-operative mapping of epileptogenic and functional networks. sEEG derived functional mapping is achieved using electrical cortical stimulations (ECS) that are currently the gold standard for delineating eloquent cortex. As this stands true especially for primary cortices (e.g., visual, sensitive, motor, etc.), ECS applied to higher order brain areas determine more subtle behavioral responses. While anterior and posterior language areas in the dorsal language stream seem to share characteristics with primary cortices, basal temporal language area (BTLA) in the ventral temporal cortex (VTC) behaves as a highly associative cortex. After a short introduction and considerations about methodological aspects of ECS using sEEG, we review the sEEG language mapping literature in this perspective. We first establish the validity of this technique to map indispensable language cortices in the dorsal language stream. Second, we highlight the contrast between the growing empirical ECS experience and the lack of understanding regarding the fundamental mechanisms underlying ECS behavioral effects, especially concerning the dispensable language cortex in the VTC. Evidences for considering network architecture as determinant for ECS behavioral response complexities are discussed. Further, we address the importance of designing new research in network organization of language as this could enhance ECS ability to map interindividual variability, pathology driven reorganization, and ultimately identify network resilience markers in order to better predict post-operative language deficit. Finally, based on a whole body of available studies, we believe there is strong evidence to consider sEEG as a valid, safe and reliable method for defining eloquent language cortices although there have been no proper comparisons between surgical resections with or without extra-operative or intra-operative language mapping.